PENGARUH PENGGUNAAN GADGET TERHADAP DEGRADASI KETAJAMAN PENGLIHATAN PADA ANAK USIA SEKOLAH DI SDN 09 SUMPUR - Jannah, Raudhotul; Firman; Desyandri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The need for gadgets in today's world is increasing. Among them, 30 million children and teenagers in Indonesia use gadgets for learning and communication. The excessive frequency of gadget use is a mistake that is often ignored by many gadget users themselves. Mistakes that often occur include improper positioning and lighting intensity that is too high, resulting in a decrease in visual acuity. This also has an impact on children's difficulties in carrying out their daily activities. The purpose of this study is to analyze the effect of gadget use on the degradation of visual acuity in school-age children at SDN 09 Sumur. Using quantitative descriptive method with Cross Sectional approach. The sample size of this study was 55 people from grades 1-5. Data processing using Chi-square test with p value <0.05. The results of the analysis showed a value of p = 0.015 which means that there is an influence between light intensity and the position of gadget use on the degradation of visual acuity. However, there is no statistical effect between the frequency of screen time and the degradation of visual acuity with a value of p = 0.0112. So it can be concluded that there is an influence between the intensity of light when using gadgets on the degradation of visual acuity and there is no influence between the frequency of the duration of gadget use and the degradation of visual acuity.